2017
DOI: 10.3139/217.3264
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Molding of Linear Low Density Polyethylene (LLDPE) Fumed Silica Nanocomposites

Abstract: This paper deals with investigations of rotational molding of LLDPE – Fumed Silica (FS) nano composites. The investigations were conducted at an industrial scale using a three arm biaxial rotational molding machine by carefully monitoring the Internal Air Temperature (IAT) within the mold. The effect of 4% FS on powder flow quality (dry flow and bulk density), melt flow quality (Melt Flow Index (MFI), static mechanical properties (tensile strength, modulus, toughness, flexural strength and impact strength) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Furthermore, rotomolding can more easily handle complex shapes with a very wide range of part sizes and variable thickness, as well as easy color changes [2, 3]. These features make rotomolding to be one of the fastest growing process of the plastic industry over the last few years [4, 5]. However, some disadvantages of this process are high operating temperatures and long cycle times [68].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rotomolding can more easily handle complex shapes with a very wide range of part sizes and variable thickness, as well as easy color changes [2, 3]. These features make rotomolding to be one of the fastest growing process of the plastic industry over the last few years [4, 5]. However, some disadvantages of this process are high operating temperatures and long cycle times [68].…”
Section: Introductionmentioning
confidence: 99%
“…The superiority of the peak values obtained for both LLDPE and Glass fibre dust, was observed in the range of 15-35 percent, which was further investigated by Melt Flow Index (MFI) parameter to check the fluidity. According to the findings, 20 percent glass fibre dust concentrated with LLDPE had an optimum value of 3.16 grams/10 minutes, which is a reasonable index as needed for rotational molding processibility [2,4,23]. Shear modulus for 20 percent Glass Fibre dust added to LLDPE shows negligible significant variations, suggesting that a 20 percent LLDPE/GFD and less combination is acceptable from a rheological perspective.…”
Section: Preliminary Analysismentioning
confidence: 91%
“…Chandran et al investigated the internal air temperature, melt flow index and mechanical properties of Linear Low Density Polyethylene mixed with fumed silica for rotational molding process. They observed that 4% fumed silica proved to sustain the rotomoldability parameter while increasing the mechanical properties of the rotomolded product [23]. An E-glass fiber epoxy resin formation was prepared by Adekomaya et al using hand layup technique.…”
Section: Introductionmentioning
confidence: 99%
“…The use of rotomolding for thermosetting materials was also observed, such as epoxy resins, 39 polyurethane, 40 phenolic resins, 41 and unsaturated polyester. 1,42 Inorganic fillers used in rotomolded material include wollastonite 43 and halloysite clay, 44 calcium carbonate, 45 graphite, 30,46,47 silica, 4851 carbon nanotubes, 52 glass fibers, 5255 and carbon. 52…”
Section: Introductionmentioning
confidence: 99%
“…The use of rotomolding for thermosetting materials was also observed, such as epoxy resins, 39 polyurethane, 40 phenolic resins, 41 and unsaturated polyester. 1,42 Inorganic fillers used in rotomolded material include wollastonite 43 and halloysite clay, 44 calcium carbonate, 45 graphite, 30,46,47 silica, [48][49][50][51] carbon nanotubes, 52 glass fibers, [52][53][54][55] and carbon. 52 The organic lignocellulosic fillers studied were cabuya (Andean sisal, Furcraea cabuya) 11 and sisal (Agave sisalana); 11,15 wood fiber; 12 flax; 15 oil palm empty fruit bunch; 56 agave (sisal species native to Central America, Agave tequilana); 13,14,57,58 pine wood; 59 coir, 59 maple wood; 60 banana and abaca´; 61 maple; 3,62 and hemp.…”
Section: Introductionmentioning
confidence: 99%